The Increment of Choroidal Thickness in Euthyroid Graves’ Ophthalmopathy: Is It an Early Sign of Venous Congestion? - Eylem Cagiltay; Fahrettin Akay; Ozgur Demir; Erdinç Aydın; Berkay Akmaz; Baris Pamuk (Journal of Ophthalmology)
Objective. Clinical manifestations of Graves’ ophthalmopathy (GO) are caused by the overcompression of orbital tissues within the restricted orbital bone cavity. Impaired ocular blood flow may disrupt the retinal microstructure and functions. In this study, we aimed to investigate the macular and choroidal thickness changes in GO compared with healthy subjects. Materials and Methods. The study group comprised 50 adult patients with previously diagnosed Graves’ disease with ophthalmopathy who were on antithyroid treatment. For the assessment of GO activity, the VISA (vision, inflammation, strabismus, and appearance) inflammatory score was used. When euthyroidism was achieved without side effects, the patients were referred to the ophthalmology clinic for spectral-domain optical coherence tomography (SD-OCT) evaluation. Results. Subfoveal, mean, and temporal choroidal thicknesses were increased significantly in the study group according to the controls. The mean choroidal thickness was elevated. Conclusions. This elevation is because of the intraorbital inflammation even in this nonsevere GO group. Choroidal thickness might be affected from the venous obstruction and congestion in patients with GO. The elevation of the choroidal thickness might be an early sign of venous congestion that occurs before the elevation of intraocular pressure.